The importance of dietary HUFA for meagre larvae (Argyrosomus regius; Asso, 1801) and its relation with antioxidant vitamins E and C. (12th October 2015) - El Kertaoui, Najlae; Hernández‐Cruz, Carmen María; Montero, Daniel; Caballero, María José; Saleh, Reda; Afonso, Juan Manuel; Izquierdo, Marisol
Abstract: Despite the interest of meagre ( Argyrosomus regius ) as a fast‐growing candidate for Mediterranean aquaculture diversification, there is a lack of information on nutrition along larval development. Importance of highly unsaturated fatty acids (HUFA) and the antioxidant vitamins E and vitamin C has not been investigated yet in this species. Six diets with two levels of HUFA (0.4% and 3% dw), two of vitamin E (1500 and 3000 mg kg −1 ) and two of vitamin C (1800 and 3600 mg kg −1 ) were fed to 15 dah meagre larvae. Larval growth in total length and dry body weight was significantly lowest in larvae fed diet 0.4/150/180 and showed few lipid droplets in enterocytes and hepatocytes and lower HUFA contents than the initial larvae. Increase in dietary HUFA up to 3%, significantly improved larval growth and lipid absorption and deposition. Besides, among fish fed 3% HUFA, increase in vitamin E and vitamin C significantly improved body weight, as well as total lipid, 22:6n‐3 and n‐3 fatty acids contents in the larvae. Thus, the results showed that 0.4% dietary HUFA is not enough to cover the essential fatty acid requirements of larval meagre and a high HUFA requirement in weaning diets is foreseen for this species. Besides, the results also pointed out the importance of dietary vitamin E and C to protect these essential fatty acids from oxidation, increase their contents in the larvae and promote growth, suggesting high vitamin E and C requirements in meagre larvae (higher than 1500 and 1800 mg kg −1 for vitamin E and vitamin C respectively).